PENERAPAN ALGORITMA DECISION TREE, SVM, NAÏVE BAYES DALAM DETEKSI STUNTING PADA BALITA - Hanif, Kharis Hudaiby; Muntiari, Novita Ranti (Universitas Methodist Indonesia, 2024)
Stunting is a toddler's body condition that is short according to body length according to age (PB/U), ≤ 2 Standard Deviations (SD), with a z-score between -3 standard deviations (SD). Where checking the stunting status of toddlers takes quite a long time because it is done manually and is also prone to errors. Therefore, it is hoped that a system can classify toddler examination data quickly and accurately to predict children's stunting status. Building a system that uses an algorithm to classify the stunting status of toddlers usingdecision tree, naïve bayes, andSVM. With what level of accuracy is the best of the 3 algorithms? Results from testing with 30% testing data and 70% training data using an algorithmdecision tree, naïve bayes, and SVM. Accuracy level test resultsdecision tree by 99%,naïve bayes of 48%, and SVM of 95%. So, the algorithm with the highest level of accuracy isdecision tree amounts to 99%. Wallet hiredecision tree better for detecting stunting in toddlers